2020
DOI: 10.1002/prot.26012
|View full text |Cite
|
Sign up to set email alerts
|

Studying dynamics without explicit dynamics: A structure‐based study of the export mechanism by AcrB

Abstract: RND family proteins are transmembrane proteins identified as large spectrum drug transporters involved in multi-drug resistance. A prototypical case in this superfamily, responsible for antibiotic resistance in selected gram negative bacteria, is AcrB. AcrB forms a trimer using the proton motive force to efflux drugs, implementing a functional rotation mechanism. Unfortunately, the size of the system (1049 amino-acid per monomer and membrane) has prevented a systematic dynamical exploration, so that the mild u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In comparison, cationic antibiotics such as oleandomycin, erythromycin, and puromycin are pumped out with low efficiency (Tikhonova et al, 2002). The observed changes in electrostatic potential surfaces of AP L and DP T among pre-MD and most populated cluster structures are related to (expected) conformational changes taking place in the transporters during the MD simulations (Simsir et al, 2021).…”
Section: Discussion and Perspectivesmentioning
confidence: 95%
“…In comparison, cationic antibiotics such as oleandomycin, erythromycin, and puromycin are pumped out with low efficiency (Tikhonova et al, 2002). The observed changes in electrostatic potential surfaces of AP L and DP T among pre-MD and most populated cluster structures are related to (expected) conformational changes taking place in the transporters during the MD simulations (Simsir et al, 2021).…”
Section: Discussion and Perspectivesmentioning
confidence: 95%
“…Currently, AcrAB-TolC is the only drug efflux pump for which there are high-resolution structures of the whole pump assembly in a resting and transport state, and these offer structural insight into the pump’s mechanism of action [ 13 ]. Molecular dynamics (MD) simulations have also been used to study AcrAB-TolC’s conformational change, particularly the functionally rotating mechanism of AcrB [ 31 , 32 ]. This was complemented by a recent study of numerous X-ray structures of AcrB with different substrates that revealed several intermediate states of the transport cycle [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…leave) the active site [1]. Membrane transporters implement complex efflux mechanisms resorting to loops changing the relative position of (essentially) rigid domains [2]. In the humoral immune response, the binding affinity of antibodies for antigens is modulated by the dynamics of loops called complementarity determining regions (CDRs) [3].…”
Section: Introductionmentioning
confidence: 99%